Prevalence of Contraceptive Non-use Due to Husbands/Partners Influence Among Married Women in Ethiopia: A Multilevel Analysis Using Demographic and Health Survey 2016 Data - Asratie, Melaku Hunie; Kassie, Belayneh Ayanaw; Belay, Daniel Gashaneh (Frontiers in Reproductive Health, 2022)
Background: In Ethiopia women with their husbands/partners are the decision-makers for contraceptives non-use suffered either due to the consequence of unintended pregnancy or due to the indirect impact of the secret use of contraceptives from their husbands/partners. Despite this challenge, there is a dearth of evidence about the magnitude of husbands/partners' decision-maker on contraceptives non-used in Ethiopia. Objective: This study was aimed to assess the magnitude of husbands'/partners decisions on contraceptive non-use and associated factors among married and non-contraceptive user reproductive-age women in Ethiopia. Methods: The study used Ethiopian Demographic and Health Survey 2016 data which was a cross-sectional survey from 18th of January 2016 to 27th of June 2016. A total weighted sample size of 5458 married women was taken. A multilevel logistic regression model was fitted. Variables with a p-value of ≤0.2 in the bivariable were taken to multivariable analysis. Adjusted odds ratio with 95% confidence interval was used, and variables with a p-value of <0.05 were considered as statistically significant with the outcome variable. Results: Husband decision-making power on contraceptive non-use was 10.44%. Husband educational level higher (Adjusted Odds Ratio (AOR=2.6; CI 1.4-4.7), being Muslim, protestant, and others in religion (AOR=2.4; CI (Confidence Interval) 1.7-3.5), (AOR=2.1; CI 1.4-3.1), (AOR=4.5; CI 2.3-8.5) respectively, media exposure (AOR=1.4; CI 1.0-1.8), husband wants more children (AOR=3.7; CI 2.8-4.8), husband desire didn’t know (AOR=1.4; CI 1.1-1.9), information about family planning (AOR=0.6; CI 0.4-0.8), visited by field worker (AOR=0.7; CI 0.5-0.9), visited health facility (AOR=0.6; CI 0.4-0.7), and community husband education high (AOR=1.6; CI 1.1-2.4) were statistically significant with husband decision making power on contraceptive non-use. Conclusions: In Ethiopia 1 out of 10 married women is influenced by their husband/partner's decision-making power of non-use contraceptives. Husband educational level high, religion (Muslim, protestant, and others), media exposure, husband desire for children (husband wants more and don’t know), and community husband education were variables positively associated with the outcome variable; whereas having information about family planning, visited by field worker, and visited health facility were negatively associated husband decision making power for non-use contraceptive in Ethiopia.